1993
DOI: 10.1063/1.353658
|View full text |Cite
|
Sign up to set email alerts
|

Soft magnetic properties of composite-anisotropy CoNbZr/ceramics multilayers (invited)

Abstract: CoNbZr/ceramics multilayered films, the metal layers of which have sequentially changed anisotropy directions, were investigated. Such newly processed film is called ‘‘composite-anisotropy multilayer film.’’ The effects of this new processing on soft magnetic properties were studied. In the case where the shift angle in the easy magnetization direction between neighboring CoNbZr layers is 45°, a smooth B-H loop with low coercivity was obtained. Furthermore, annealing from 200 to 400 °C resulted in high permeab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…For example, a high permeability is only available when excitation magnetic field is along the magnetic hard-axis (HA) direction, i.e. HA excitation [16]- [18]. This restricts the efficiency of SFMs to only 50% for the UMA SFMs when the SFMs cover on the plane of microinductors.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, a high permeability is only available when excitation magnetic field is along the magnetic hard-axis (HA) direction, i.e. HA excitation [16]- [18]. This restricts the efficiency of SFMs to only 50% for the UMA SFMs when the SFMs cover on the plane of microinductors.…”
Section: Introductionmentioning
confidence: 97%
“…For this purpose, Sugawara et al [16] fabricated composite anisotropy multilayer films using the multilayering method in which many magnetic thin layers with constant uniaxial anisotropy were piled up with the anisotropic axes being shifted sequentially from bottom to surface so as to cancel out the overall anisotropy [16]. Chai et al [19] reported an omnidirectional rotatable anisotropy in ferrite doped CoFe thin film.…”
Section: Introductionmentioning
confidence: 99%
“…To find the desired materials with IHP in the GHz range is still a challenge. For instance, a variety of theoretical 5 6 7 and experimental works focus on both high 8 9 10 and isotropic 11 12 13 14 15 16 17 18 permeability in the GHz range of granular films 9 and multilayers 10 of magnetic alloys, ferrites and their composites.…”
mentioning
confidence: 99%
“…Searching for the isotropic permeability in the GHz range is another important topic in magnetic thin films. For instance, magnetic thin films with rotatable stripe domain 42 43 44 45 46 , composite-anisotropy multilayer as well as crossed anisotropies multilayer 11 12 13 14 15 16 17 18 are intensively investigated. The rotatable stripe domain was discovered firstly in Permalloy films in 1961 42 , and then in many other magnetic thin films 43 44 45 46 .…”
mentioning
confidence: 99%
“…3 In recent decades, high-frequency soft magnetic thin films have been extensively studied because of their potential suitability as noise suppressors for ultrasmall integrated circuit chip modules. In particular, Co alloy amorphous films 4,5 and Co metal-oxide granular films 3,6 have attracted significant attention owing to their high saturation magnetization and soft magnetic properties at high frequencies. These conventional films exhibiting uniaxial magnetic anisotropy have shown high-frequency soft magnetic performance, which unfortunately degraded when the effective electromagnetic field direction deflected from its hard axis, limiting their application to uniaxial devices.…”
Section: Introductionmentioning
confidence: 99%